Assistance in Cost Classification and Cost Production of Street Food Microenterprises in Bekasi District - Neng Asiah; Hendri Kartika Andri; Sabaruddinsah; Amara Pristania Nandita; Aisah Indah Safitri (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
MSMEs are considered the main pillar of the economy, especially when large companies experience difficulties or bankruptcy. This is considered positive because MSMEs can be the main indicator of regional economic progress. However, some MSME players may not understand how to develop their products, especially in classifying and calculating costs. One strategy in business development is to make a detailed cost classification or calculation of production costs in an activity report. This activity aims to provide practical guidance, training and mentoring in classifying costs and calculating production costs for MSMEs in the Mustika Jaya forum, especially "Kaki Street Food" business owners. This activity involved developing a step-by-step guide to help "Kaki Street Food" business owners understand the cost classification and production costs involved in their business. The guide covers important aspects such as market analysis, marketing strategy, and financial planning. The results of the activity provide an understanding to partners about the importance of classifying costs in supporting the preparation of production cost reports which can ultimately be used as a basis for decision-making on setting selling prices. Partners can participate in the activity well, as evidenced by the results of the simulation of the preparation of production cost reports that are done independently.